2020
DOI: 10.21203/rs.3.rs-91179/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Short Chain Fatty Acids (SCFAs) Modulation on Potentially Diarrhea Causing Pathogens in Yaks Through Metagenomics Sequencing

Abstract: Yaks are of great importance on the plateau; however, an emerging endemic diarrheal disease during the last few years is posing a great threat to the health of these animals. Yaks have special gut microbiotal community and short-chain fatty acids (SCFAs) which are not only the principle nutrient substrates of intestinal epithelial cells but can also regulate the epithelial barrier. Until now, metagenomics sequencing has not been reported in diarrheal yaks. A scarce information is available regarding the levels… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
(108 reference statements)
1
0
0
Order By: Relevance
“…Our results showed that pathogenic E. coli induced calf diarrhea, and the contents of SCFAs in feces were significantly lower than those of healthy calves in the NG, such as acetic acid, propionic acid, butyric acid, and total acid. This is consistent with the findings of Li et al, who identified that the content of SCFAs in the feces of diarrhea-type yaks was significantly lower than that of healthy yaks [48]. Through correlation analysis of the bacteria with significant differences in the abundance and content of SCFAs, we can further demonstrate that calf diarrhea induced by pathogenic E. coli affects intestinal florae-particularly reducing SCFAs and producing bacteria abundance-thereby affecting the production of SCFAs.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that pathogenic E. coli induced calf diarrhea, and the contents of SCFAs in feces were significantly lower than those of healthy calves in the NG, such as acetic acid, propionic acid, butyric acid, and total acid. This is consistent with the findings of Li et al, who identified that the content of SCFAs in the feces of diarrhea-type yaks was significantly lower than that of healthy yaks [48]. Through correlation analysis of the bacteria with significant differences in the abundance and content of SCFAs, we can further demonstrate that calf diarrhea induced by pathogenic E. coli affects intestinal florae-particularly reducing SCFAs and producing bacteria abundance-thereby affecting the production of SCFAs.…”
Section: Discussionsupporting
confidence: 92%